Emergence of Nano-Dentistry as a Reality of Contemporary Dentistry - Orest Kochan; Svitlana Boitsaniuk; Mariana Levkiv; Krzysztof Przystupa; Nadiia Manashchuk; Khrystyna Pohoretska; Natalia Chornij; Iryna Tsvyntarna; Liudmyla Patskan (Applied Sciences, 2022)
(1) Background. Nanotechnology offers significant alternative ways to solve scientific, medical, and human health issues. Dental biomaterials were improved by nanotechnology. It manufactures better materials or improves the existing ones and forms the basis of novel methods for disease diagnosis and prevention. Modern nanotechnology makes oral health care services more acceptable for patients. Nanotechnology is now important area of research, covering a broad range of applications in dentistry. (2) Methods. Relevant literature from Scopus published in English was selected using the keywords “nanoparticle” and “dentistry”. To the selected articles we applied the inclusion and exclusion criteria to choose the relevant ones. (3) Results. Based on the relevant articles, a literature review was prepared. This review provides an insight into the applications of nanotechnology in various branches of dentistry. We applied several regression models to fit number of papers versus time and chose the best one. We used it to construct the forecast and its 95%-confidence interval for the number of publications in 2022–2026. (4) Conclusions. It shows that a significant rise in papers is expected. This review familiarizes dentists with properties and benefits of nanomaterials and nanotechnology. Additionally, it can help scientists to consider the direction of their research and to plan prospective research projects.